2019
DOI: 10.1007/s41105-019-00224-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ramelteon on insomnia severity: evaluation of patient characteristics affecting treatment response

Abstract: We conducted a multicenter, open-label, observational study to evaluate the effectiveness and safety of ramelteon in patients with insomnia, and patient characteristics affecting treatment response in routine clinical practice. Eligible patients were aged ≥ 20 years, had a diagnosis of insomnia with difficulty falling asleep, and were scheduled to receive ramelteon 8 mg/day for 12 weeks. The primary objective was to evaluate the relationship between changes in insomnia severity [measured by the Insomnia Severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Liu et al [ 44 ] is a systematic review and a meta-analysis that included studies published up to 2011 and only included RCTs focused on ramelteon only versus placebo among adults. While a 2014 meta-analysis [ 17 ] addressed efficacy and safety of ramelteon in adults and another Ferracioli-Oda et al [ 19 ] is a meta-analysis that addressed melatonin usage in adults and children with primary sleep disorders, neither search went beyond 2012. In comparison, the current systematic review and meta-analyses included all studies using comparative design involving older adults, a high-risk population with insomnia with searches conducted to 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [ 44 ] is a systematic review and a meta-analysis that included studies published up to 2011 and only included RCTs focused on ramelteon only versus placebo among adults. While a 2014 meta-analysis [ 17 ] addressed efficacy and safety of ramelteon in adults and another Ferracioli-Oda et al [ 19 ] is a meta-analysis that addressed melatonin usage in adults and children with primary sleep disorders, neither search went beyond 2012. In comparison, the current systematic review and meta-analyses included all studies using comparative design involving older adults, a high-risk population with insomnia with searches conducted to 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Ramelteon is a novel melatonin MT1 and MT2 receptor subtypes agonist that has specific effects on melatonin receptors in the suprachiasmatic nucleus [ 16 ]. Clinical investigations and post-marketing surveillance of ramelteon have found this drug be to be safe in patients with insomnia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may have been because comorbid depression was rare and baseline anxiety/depression scores were not high among the patients included in our study. In another observational study of ramelteon for insomnia, 29 patients aged ⩾75 years showed a higher OR Acupuncture in Medicine, 42 (2) for responders versus non-responders. Moreover, patients with severe insomnia showed a higher tendency to respond.…”
Section: Response and Remission Predictors For Insomnia Treatmentmentioning
confidence: 91%
“…The ISI showed a mean score reduction of −5.0 points in 1527 patients in an open‐label trial of ramelteon over 12 weeks (145). In a randomized double‐blind control trial, among patients receiving eszopiclone, the mean ISI score decreased from 17.9 points to 8.3 points (improvement), whereas in patients on a placebo, the ISI score decreased from a mean of 17.8 points to 12.9 points at 6 months ( P < 0.0001 for the difference between groups) (146).…”
Section: Insomnia Severity Indexmentioning
confidence: 99%